Pengaruh Program Pelatihan dan Motivasi terhadap Prestasi karyawan pada PT. Mubarokfood Kudus - Muhammad Faisal Zain; Rohmat Saragih (Universitas Batanghari Jambi, 2023)
The assessment of an employee's performance is closely related to the competence of the employee, low competence can be improved and developed through various means such as holding training and motivation in the employee. This study discusses the relationship between work motivation and work performance owned by employees of PT MubarokFood Kudus. The research uses a descriptive qualitative approach method. The subjects of this study were employees of PT MubarokFood Kudus which is located in Kudus Regency which totals 108 people. Scoring in this study uses a likert scale, then the data collection technique uses observation, interviews, and Fieldnotes or field notes. In this study, using multiple regression analysis using IBM SPSS software data processing and obtaining t test results, namely training variables affecting employee performance. This can be interpreted to mean that the training held by the company can improve the performance of PT Mubarokfood employees. Furthermore, it is known that in the F test, the training and motivation variables simultaneously affect the employee performance variables, so it can be said that the training and motivation provided by PT Mubarokfood will provide simultaneous impact on employee performance later. So that in the coefficient of determination, it can be concluded that the training and motivation variables have an effect of 15.1% on employee performance variables, with the remaining 84.9% influenced by other factors that were not studied in this study.